A Thematic and Stylistic Analysis of John Milton’s Paradise Lost - Betu, Donat Nkuna; Adolphe KAYEMBE MUATA; Augustin TSHIAMU TSHIAMU (RADINKA JAYA UTAMA PUBLISHER, 2024)
This article aims to explore John Milton’s poetic theme and style in his epic poem “Paradise Lost” Paradise Lost is an epic poem in blank verse. It explores the biblical story of the fall of man, focusing primarily on the rebellion of Satan and the expulsion of Adam and Eve from the Garden of Eden. From the background above, this research aims to explain the theory of a thematic and stylistic analysis of John Milton's Paradise Lost. The method used is a literature review, which includes the analysis and evaluation of scientific articles and journals that are relevant to the research problem. This research explains the thematic study of the poem; we analyzed themes and gave significant clues about them. Finally, we tackled the style used by the author in the poem. Concerning the style, we have noticed that Milton's writing style in Paradise Lost is characterized by its elaborate use of figurative language, including epic similes, vivid imagery, and intricate metaphors.